Educating contemporary performing artists: research/creation, socio-constructivist learning and psychoanalytic ethics - Causillas, Tirso (2024)
The following article explores the relationship between research/creation, the socio- constructivist perspective of learning and psychoanalytic ethics, with the goal of proposing key points for a debate on the education of contemporary performing artists. Considering that it is essential to build a space for critical and creative dialogue that facilitates learning from research, the article addresses and problematizes the so-called dogmatic image of art and the teacher/disciple model to approach research/creation as an educational strategy, which is generator of knowledge and, at the same time, a fertile space for ethical debate around the very limits of scenic practice.